Physicochemical properties, nutrient profile, microbial stability, and sensory evaluation of cupcakes enriched with pomegranate seed oil - Lydia, D. Esther; Mohandas, Anuja; Priya, Shanmugha; Monica, Sarah Jane; Gajdács, Márió; Khusro, Ameer; Alghamdi, Saad; Almehmadi, Mazen; Kahrizi, Danial; Sahibzada, Muhammad Umar Khayam (Cellular and Molecular Biology, 2022)
Excessive use of refined flour, solid fats, and sugar in preparing baked products are considered to be unhealthy and is intricately linked with the development of lifestyle diseases. Replacing refined flour with whole wheat flour and solid fats with cold-pressed oil serves as an alternate option. The study was aimed at evaluating the physicochemical properties, nutrient composition, sensory attributes, and shelf life of cupcakes enriched using pomegranate seed oil (PSO). Vanilla and chocolate cupcake variants were prepared using 25 and 50% of PSO. A sensory panel consisting of 30 semi-trained participants was selected for evaluating the formulated products using a five-point hedonic scale. Nutrient content was estimated using standard techniques. The stability of the formulated product was determined by evaluating the physicochemical traits and microbial growth on the 0th, 4th, and 7th day. Mean scores of the sensorial analysis showed that the incorporation of PSO in cupcakes was highly accepted by the panel members. Chocolate cupcake containing 50% of PSO was found to be the most preferred product (3.53±0.94), followed by vanilla cupcake containing 25% of PSO (3.4±0.62). The moisture, protein, and fat content of chocolate cupcakes containing 25% of PSO were high. Cupcakes prepared with PSO can be stored for four days at room temperature. GC-MS analysis showed the presence of punicic acid, oleic acid, tocopherols, campesterol, sitosterols, stigmasterol, and α-tocopheryl acetate as pre-dominant fatty acid in unheated and heated PSO. In conclusion, cupcakes prepared using PSO showed acceptable physicochemical qualities and sensory properties which indicated its successful consumption by people affected with metabolic disorders.